PAK5, a New Brain-Specific Kinase, Promotes Neurite Outgrowth in N1E-115 Cells - Dan, Chuntao (American Society for Microbiology, 2002)
We have characterized a new member of the mammalian PAK family of serine/threonine kinases, PAK5, which is a novel target of the Rho GTPases Cdc42 and Rac. The kinase domain and GTPase-binding domain (GBD) of PAK5 are most closely related in sequence to those of mammalian PAK4. Outside of these domains, however, PAK5 is completely different in sequence from any known mammalian proteins. PAK5 does share considerable sequence homology with the Drosophila MBT protein (for “mushroom body tiny”), however, which is thought to play a role in development of cells in Drosophila brain. Interestingly, PAK5 is highly expressed in mammalian brain and is not expressed in most other tissues. We have found that PAK5, like Cdc42, promotes the induction of filopodia. In N1E-115 neuroblastoma cells, expression of PAK5 also triggered the induction of neurite-like processes, and a dominant-negative PAK5 mutant inhibited neurite outgrowth. Expression of activated PAK1 caused no noticeable changes in these cells. An activated mutant of PAK5 had an even more dramatic effect than wild-type PAK5, indicating that the morphologic changes induced by PAK5 are directly related to its kinase activity. Although PAK5 activates the JNK pathway, dominant-negative JNK did not inhibit neurite outgrowth. In contrast, the induction of neurites by PAK5 was abolished by expression of activated RhoA. Previous work has shown that Cdc42 and Rac promote neurite outgrowth by a pathway that is antagonistic to Rho. Our results suggest, therefore, that PAK5 operates downstream to Cdc42 and Rac and antagonizes Rho in the pathway, leading to neurite development.